Integrative taxonomy of a new species of Rhyacodrilus (Annelida: Clitellata: Rhyacodrilinae) from Tibet Plateau rivers, with a preliminary assessment of its phylogenetic position - Jiang, Wei; Zhou, Tingting; Wang, Hongzhu; Erséus, Christer; Cui, Yongde (Zootaxa, 2023)
A new Qinghai-Tibet Plateau species, Rhyacodrilus tanggulaensis Jiang & Cui sp. nov. (Annelida, Clitellata, Naididae, Rhyacodrilinae), is described, and its phylogenetic relationships within the genus is assessed on the basis of both mitochondrial (16S rDNA, COⅠ gene) and nuclear (ITS2) markers. Data from 32 species of Naididae, representing 7 subfamilies and 25 genera are used. Ten species were chosen as outgroup taxa. The molecular data were analyzed by Bayesian inference. The new species is distinguished from other species of Rhyacodrilus by the following combination of characters: dorsal and ventral chaetae with distal tooth 2–3 times longer than proximal, spermathecal and penial chaetae present, atria long and tubular, atrial duct conspicuous. The analyses of the combined molecular data corroborate the close relationship between Naidinae and the rhyacodriline genera Rhyacodrilus, Monopylephorus, and Ainudrilus, and show that the new species is more closely related to R. falciformis, R pigueti, R. okamikae and R. subterraneus, than to R. sinicus, another Chinese species, R. hiemalis and R. coccineus.